Evaluasi Kebijakan Pemasaran Dana KUR di Bank Sumsel Babel Cabang Kota Pagar Alam - zarra, aini; Deni Priansyah (SAUJANA : Jurnal Perbankan Syariah dan Ekonomi Syariah, 2025)
The KUR program is a financing or credit program provided by the government through banking to micro, small and medium enterprises (UMKM), this program was launched by the government as a form of government support in increasing access to financing for the small business sector. This study aims to evaluate the marketing policy of People's Business Credit (KUR) funds implemented by Bank Sumsel Babel, Pagaralam City branch. The focus of the evaluation includes marketing strategies, the effectiveness of policy implementation, and obstacles faced in distributing KUR funds to micro, small and medium enterprises (UMKM). The research method used is a qualitative method with data collection techniques through interviews, observations, and documentation studies. The results of the study indicate that the marketing strategy for KUR funds implemented is quite effective in increasing credit distribution, but there are still several obstacles such as a lack of public understanding of KUR products and limited marketing resources. This study recommends increasing socialization and strengthening cooperation with related parties to optimize the distribution of KUR funds in the Pagar Alam area. Keywords: Policy evaluation, marketing, KUR funds, Bank Sumsel Babel, UMKM